Watch IT: The risks and promises of new information technologies. Nicholas C. Burbules, Thomas A. Callister (h) : Ediciones Granica S. A., 2001 - Gorga, Gladys (2004)
Se realiza una reseña del libro capítulo por capítulo. Los títulos de los capítulos son (en inglés): Chapter 1 - The Risky Promises and Promising Risks of New Information Technologies for Education Chapter 2 - Dilemmas of Access and Credibility: Access for Whom? Access to What? Chapter 3 - Hypertext: Knowledge at the Crossroads Chapter 4 - Critical reading on Internet Chapter 5 - Misinformation, Malinformation, Messed-Up Information, and Mostly Useless Information: Is Censorship the Best Response? Chapter 6 - Surveillance & Privacy: Can Technology Protect What Technology Takes Away? Chapter 7 - Information for sale: Commercialization & the Educational Potential of the Internet Chapter 8 - What Kind of Community Can the Internet Be?